Effect of phytase supplementations on the performance of Babcock-380 Layer Hens - Md. Ruhul Amin; Elliyana Nadia Hamidi (Universiti Malaysia Kelantan, 2013)
In order to examine the effect of phytase supplementation in the diet of laying hen this experiment was conducted with 30 commercial hybrid Babcock-380 layers of 73 weeks of age. The hens were grouped into 3 treatment groups and given microbial phytase (Rena Phytase 400) at levels 2.5, 1.5 and 0 (control) g/kg feed in addition to their basal diet (110 g commercial pellet/day). Records on egg production/group/day, egg mass weight/day, body weight of hens at the end of experimental period were taken and analysed. Results revealed that hen house egg production (HHEP) and egg weight (EW) varied (p<0.05) among the treatment groups but level of phytase did not affect (p<0.05) body weight of hens. Both HHEP and EW were in order of 2.5>1.5>0 g/kg feed phytase group and all the means were significantly (p<0.05) different from each other within treatment groups. Microbial phytase supplementation in layer ration proved to be beneficial in terms of egg production and egg size even after 72 weeks of age of hens. Layer farms in Malaysia can use this technology to earn more profit.